PERILAKU PETANI LADANG BERPINDAH DI KANAGARIAN RABI JONGGOR KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN BARAT - Yenni, Malida; Bakaruddin, Bakaruddin; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
This study aimed to obtain information, analyze and describe data on Farmers Field Switching Behavior in Kanagarian Rabbi Jonggor, judging from the determination of the location, processing, maintenance, leaving the land factor. This research is qualitative research. Research subjects are determined by purposive sampling technique that is people doing shifting cultivation. Information retrieval techniques do is snowball (snowball sampling). Data was collected through observation, interviews, documentation, and then performed triangulation techniques with the data obtained from the study subjects at the time, place and situation is different. Based on this research, it was found: 1) shifting cultivation farmers behavior in determining the location of agricultural land no one wanted to define and there are not decisive. Cultivation practices carried out in the slopes and hilly areas. 2) Soil fertility has been diminished due to farmers shifting cultivation especially in land clearing is done by cut down, and cut. Tool used is a simple form of sabik, machetes and axes. The land area is cultivated and processed Ha 2/3-1 ranges around 1-4 years. 3) In the shifting cultivation without tillage. Seedlings were planted a seed locally. Planting is done using a unified tapered wood (ritual). 4) The main factor to leave the land because of soil fertility is reduced, so that the land plants can not grow well, slow crop development, the results are not satisfactory then more loss than opening a new resume. Generally abundant land in the condition untreated, currently abandoned land already cultivated a kind of old plants, there are still farmers are not planting the land to be abandoned.